Penang 500 early postcards - Cheah, Jin Seng (Editions Didier Millet, 2012)
By the late 19th century, Penang had become a thriving port trading in rubber, spices and tin. Its prosperity attracted immigrants from around the world and the island was a rich melting pot of Chinese, Indians, Malays, Europeans and many other peoples. The postcards reproduced in this book are drawn from the huge collection of Penang-born Professor Cheah Jin Seng, the author of Singapore: 500 Early Postcards, Malaya: 500 Early Postcards, Perak: 300 Early Postcards and Selangor: 300 Early Postcards.This title in the Early Postcards series will present a diverse array of picture postcards of Penang -- including of its capital George Town, now a World Heritage site -- from the 1890s to the 1970s.